THE ROLE AND IMPORTANCE OF SENTENCE STRESS IN ENGLISH AND UZBEK LANGUAGES: A COMPARATIVE LINGUISTIC STUDY (SCIENCE TIME JOURNAL, 2026)
This article examines the role and importance of sentence stress in English and Uzbek languages from a comparative linguistic perspective. It explores how sentence stress influences meaning, emphasis, and pragmatic interpretation in spoken discourse. The study also highlights the flexible and rhythm-based nature of English stress patterns compared to the relatively fixed and semantically oriented stress system in Uzbek.